2003
DOI: 10.1002/ps.799
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid tolerance in Culex pipiens pipiens var molestus from Marin County, California

Abstract: In May 2001 a sample of Culex pipiens pipiens variety molestus Forskål from Marin County, California, collected as larvae and reared to adults, was found to show reduced resmethrin and permethrin knock-down responses in bottle bioassays relative to a standard susceptible Cx. pipiens quinquefasciatus Say colony (CQ1). Larval susceptibility tests, using CQ1 as standard susceptible, indicated that the Marin mosquitoes had LC50 resistance ratios of 18.3 for permethrin, 12 for deltamethrin and 3.3 for pyrethrum. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 27 publications
5
68
0
1
Order By: Relevance
“…with increased expression of esterase activity have now been reported (Anstead et al 2007;Guerrero and Barros 2006;McAbee et al 2004;Oakeshott et al 2005). In some cases the increased activity is due to specific CarbE isozymes, but in other cases several isozymes show more intense staining.…”
Section: The Role Of Carbes In Sp Metabolism In Invertebratesmentioning
confidence: 95%
“…with increased expression of esterase activity have now been reported (Anstead et al 2007;Guerrero and Barros 2006;McAbee et al 2004;Oakeshott et al 2005). In some cases the increased activity is due to specific CarbE isozymes, but in other cases several isozymes show more intense staining.…”
Section: The Role Of Carbes In Sp Metabolism In Invertebratesmentioning
confidence: 95%
“…32,33,[38][39][40][41][42] Fonseca and others 30 found extensive hybridization (40%) between pipiens and molestus forms in the United States compared with European populations ( 10%), and a more recent study 42 found that autogenous populations in Santa Clara County, CA, were a genetic mix of f. molestus hybridized with Cx. quinquefasciatus and to a lesser extent f. pipiens.…”
Section: Introductionmentioning
confidence: 99%
“…A pyrethroidsensitive colony of Culex quinquefasciatus Say (CQ1), was used in one of the ULV trials as an additional pyrethroid susceptible control. The CQ1 strain was initially field-collected in Merced County, California, in the early 1950s and has been used at the Mosquito Control Research Laboratory, UC Davis as susceptible controls in insecticide bio-assays in the past (McAbee et al, 2004).…”
Section: Methodsmentioning
confidence: 99%